Arduino computer numerical control drawing machine - Neoh, Hock Ee (2019)
Computer Numerical Control, CNC machine is one of the most common machines that widely used in the industries nowadays. Many works that involve in movement or action that keep repeating everyday were substituted by the CNC machine from human as the human concentration becomes lower when times goes on while the product quality and quantity fabricated by machine will be maintain when times move. However, the cost of CNC machine use in industries is very high which causes the machine is not affordable in the small businesses and family use. This project is works to design a low cost Arduino based CNC machine that can perform drawing according to the given scale set by the user. The low price CNC machine is build for the small business company and family use. In this project, some types of CNC machine have been reviewed and discussed. The methodology of the hardware build, the required software and the operation flow of the machine have discussed in this project. The designs of the 3D printed components for the CNC drawing machine have been show in the result. Two types of images which are the input image and the import image have been tested. The scale of the original image and the drawn image have been compared and discussed. Two users have been invited to review on the CNC drawing machine. Future enhancements and recommendation such as the software development and the additional axis add to perform three dimensional printing have been discussed on this project